Reply to ‘Comment on “Dependence of shear wave seismoelectrics on soil textures: a numerical study in the vadose zone by F.I. Zyserman, L.B. Monachesi and L. Jouniaux” by Revil, A.’ - Zyserman, Fabio Ivan (2017)
In this paper we reply to a the comment made by Revil (2017) on our paper (2017, Geophys. J. Int., 208), where we describe seismoelectric phenomena in the vadose zone based on the theory of Pride empirically extended for unsaturated conditions. We analyse and answer each one of the enumerated critics, and reaffirm the conclusions of our work. In particular, we prove that using the conductivity model suggested by Revil (2017) does not change our predictions significantly, contrary to what was argued in the comment. Further, in the light of previous and new theoretical and experimental results existing in the literature, we confirm the reasonability of having tested a non-monotonic saturation dependent streaming potential coefficient model besides the monotonic one, and discuss the suitability of assuming a linear relation between the permeability and the excess charge.